Molecular effects of cardiac contractility modulation in patients with heart failure of ischemic aetiology uncovered by transcriptome analysis - Lyasnikova, E.; Sukhareva, K.; Vander, M.; Zaitsev, K.; Firulyova, M.; Sergushichev, A.; Sorokina, M.; Trukshina, M.; Galenko, V.; Lelyavina, T.; Mitrofanova, L.; Simonova, K.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Cardiac contractility modulation (CCM) is based on electrical stimulation of the heart without alteration of action potential and mechanical activation, the data on its fundamental molecular mechanisms are limited. Here we demonstrate clinical and physiological effect of 12 months CCM in 29 patients along with transcriptomic molecular data. Based on the CCM effect the patients were divided into two groups: responders (n = 13) and non-responders (n = 16). RNA-seq data were collected for 6 patients before and after CCM including 3 responders and 3 non-responders. The overall effect of CCM on gene expression was mainly provided by samples from the responder group and included the upregulation of the genes involved in the maintenance of proteostasis and mitochondrial structure and function. Using pathway enrichment analysis, we found that baseline myocardial tissue samples from responder group were characterized by upregulation of mitochondrial matrix-related genes, Z disc-protein encoding genes and muscle contraction-related genes. In summary, twelve months of ССM led to changes in signaling pathways associated with cellular respiration, apoptosis, and autophagy. The pattern of myocardial remodeling after CCM is associated with initial expression level of myocardial contractile proteins, adaptation reserves associated with mitochondria and low expression level of inflammatory molecules.